Analisis laporan keuangan untuk mengukur kinerja keuangan pada Kejaksaan Negeri Karanganyar - Martha Diana , Yeny (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The Karanganyar District Attorney's Office in preparing the Budget Realization Report requires analysis to measure the success of the institution's financial performance. In this study, we compare the financial performance of the Karanganyar District Attorney's Office for Fiscal Years 2019, 2020 and 2021. The arrangement of the Karanganyar State Attorney's Financial Statements refers to PP No. 71 of 2010 concerning SAK and the theorem of good financial control in government. The type of research used is descriptive qualitative research which intends to analyze the information obtained from financial reports to measure the performance of the institution. The population in this research is all information in the form of financial reports owned by the Karanganyar State Prosecutor's Office. The results showed that in 2020 there was an increase of 8.49% compared to the previous year's spending awareness. In 2021 there will be an increase of 7.25%. This is due to, among other things, the creation of capital expenditures accompanied by an increase in material expenditures to support the strategic framework that began in 2020, the accumulation of employees in order to support programs or activities and the existence of an additional ceiling of special allowances (Remuneration). Realization of Goods Expenditure in 2021 has increased by 15.60% when compared to 2020, while 2020 has decreased by 1% when compared to the previous year 2019.